RETRACTED: UNSUR KEMASLAHATAN PADA HIBAH SUAMI – ISTRI - Muhammad Zainuddin Sunarto (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2020)
RETRACTEDFollowing a rigorous, carefully concerns and considered in the review of the articlepublished in Al-Qadha: Jurnal Hukum Islam dan Perundang-Undangan entitled"UNSUR KEMASLAHATAN PADA HIBAH SUAMI – ISTRI" Vol. 7 No. 1, Juni 2020, pp.43-59, DOI: https://doi.org/10.32505/qadha.v7i1.1470. The editor found that the article had been published in jurnal Maqashid: JurnalHukum Islam Vol. 3 No. 1, Mei 2020, pp. 96-144, DOI:https://doi.org/10.35897/maqashid.v3i1.381. The document and its content have been removed from Al-Qadha: Jurnal HukumIslam dan Perundang-Undangan, and reasonable effort should be made toremove all references to this article.